PROBLEMATIKA PERANCANGAN INFRASTRUKTUR, KURATORIAL, DAN PEDAGOGI MUSEUM DI INDONESIA - Nugeraha , Mohammad Ady (Universitas Budi Luhur, 2021)
Museum is a non-profit organization to serve and build society that is open to the public. Museums are responsible to collect, conserve, investigate, communicate, and display human heritage and its environment, both tangible and intangible, for the purpose of education, research, and pleasure. According to the data published by the government in 2020, there are 439 museums in Indonesia. However, only 32 museums are included as Type A (Excellent). Meanwhile, almost 50% of the rest of the museums are yet to be evaluated. Despite the rapid growth in the number of museums in recent years, this data indicates the lack of design, management, and supervision of museums in Indonesia. This research is qualitative and descriptive research that observes a number of museums in major cities to identify general problems of museum’s design and management. The result is evaluated through common practice of international museums as well as encompassing regulations. This research categorizes these problems into infrastructure and spatial design, narrative and curatorial, and pedagogy and visitor’s interaction. With the cultural diversity and abundance of natural resources in Indonesia, proper design and management could maximize museum’s potential as means of conserving humanity’s heritage, informal education, recreation, as well as driving economic and cultural-tourism activities.